A coated of Ca/Fe layered hydroxide onto a synthesized adsorbent from (banana peels) for removal of cadmium from simulated wastewater - Hayder M. Abdul-Hameed (Caspian Journal of Environmental Sciences, 2021)
Ca/Fe layered hydroxide (LH) coated with a produced adsorbent was synthesized and characterized by adsorbent from banana peels by a co-precipitation method. The SEM and EDS tests revealed that the particles on the surface of the adsorbent extra-fine, well spread, and the structure of LHs is heterogeneous. The contents of the Fe and Ca after the process increase well according to the EDS analysis. From analysis, it was an enhancement in the specific surface area of the adsorbent from 44.39 m2 g-1 (before synthesizing) to 1022.08 m2 g-1 (after synthesizing). The produced Ca/Fe LH was used for the removal of (Cd++) from aqueous solution; a series of the batch experiments with different dynamic parameters reveals the best removal efficiency of (93.4%) for a (Ca /Fe molar ratio of 2).